How does economic policy uncertainty affect corporate debt maturity? - Xiang Li; Dan Su (Halle Institute for Economic Research (IWH), 2020)
This paper investigates whether and how economic policy uncertainty affects corporate debt maturity. Using a cross-country firm-level dataset for France, Germany, Spain, and Italy from 1996 to 2010, we find that an increase in economic policy uncertainty is significantly associated with a shortened debt maturity. Specifically, a 1% increase in economic policy uncertainty is associated with a 0.22% decrease in the long-term debt-to-assets ratio and a 0.08% decrease in debt maturity. Moreover, the impacts of economic policy uncertainty are stronger for innovation-intensive firms. We use firms' flexibility in changing debt maturity and the deviation to leverage target to gauge the causal relationship, and identify the reduced investment and steepened term structure as transmission mechanisms.
urn:nbn:de:101:1-2020071510474068900192; Additional information: A completely revised version of this paper has been published as Li, Xiang: How Does Economic Policy Uncertainty Affect Corporate Debt Maturity? IWH Discussion Papers 5/2022. Halle (Saale) 2021: http://hdl.handle.net/10419/249745; More recent version: http://hdl.handle.net/10419/249745
Keywords: D81; G32; 330; economic policy uncertainty; debt maturity; capital structure; corporate investment